The Investigation of the Drivers of Gender Inequality in Developed and Developing Countries - OLAOSEBIKAN, Oluwabusola Ikeoluwa; AWOYEMI, Bosede Olanike; IGBATAYO, Samuel Aderemi (The Gender Truth Journal, 2025)
Gender inequality continues to pose significant challenges to inclusive development, undermining social, economic, and health progress across countries. This paper examines the drivers of gender inequality across 15 developed and 54 developing countries over the period 2000–2024, with the primary aim of analysing how socioeconomic, demographic, and health-related factors influence the Gender Inequality Index (GII). Using annual panel data, the study employs dynamic panel methods, including Feasible Generalized Least Squares (FGLS), Panel-Corrected Standard Errors (PCSEs), and Driscoll–Kraay corrections, to account for cross-sectional dependence, slope heterogeneity, and non-stationarity. The model specifies GII as a function of education gaps, labour-force participation and employment disparities, wage and salaried-worker gaps, public health spending, infant mortality, immunization coverage, GDP per capita, and urbanization. The results reveal that in developed countries, gender inequality is significantly aggravated by wider education and employment gaps, larger labourforce participation and wage disparities, higher infant mortality, and rapid urban growth, whereas higher GDP per capita and broader immunization coverage mitigate inequality. In developing countries, the education gap, labour-force gap, wage gap, and infant mortality emerge as strong positive drivers of inequality, while GDP per capita, increased public health expenditure, and urbanization contribute to reducing it; the impact of immunization is weak and mixed, and the employment gap shows estimator-dependent significance. The findings underscore that although certain determinants are common across countries, their effects vary in intensity depending on the level of development. The study concludes that targeted interventions such as closing educational and employment disparities, formalizing labour markets, improving job quality, and strengthening health systems through sustainable financing are essential to narrowing gender gaps. The contribution of this paper lies in providing comparative empirical evidence that deepens the understanding of the context-specific dynamics of gender inequality and in proposing multi-dimensional policy frameworks relevant to both developed and developing economies.